Tindak Tutur dalam Negosiasi Lamaran Pernikahan di Kabupaten Soppeng - Haslinda Haslinda; Ika Sastrawati (STKIP Andi Matappa Pangkep, 2021)
The purpose of this study is to describe the intent and meaning of a speech act in the marriage proposal procession in Soppeng district. This study is a qualitative type of data source in this study in the form of recordings of conversational application processions from marriage in Soppeng district and will be analyzed into speech acts in general. The data collection technique used is the recording and note-taking technique, by listening repeatedly to the results of a recording of the conversations of the two parties in the marriage proposal procession. The results in this study confirmed that, there were 24 different speech acts which were classified as locutionary, illocutionary, perlocutionary speech acts which were analyzed by the researcher. The results showed that 11 were classified as locutionary speech acts, 6 were classified as illocutionary speech acts, and 7 were classified as perlocutionary speech acts.